Potentially inappropriate prescribing among older adults with hypertension in China: prevalence and related comorbidities across different outpatient settings - Chen, Jiaqi; Wang, Shuang; Lu, Lvliang; Yang, Yujie; Wang, Kai; Zheng, Jing; Zhou, Zhijiang; Guo, Pi; Cai, Yunpeng; Zhang, Qingying (Frontiers in Pharmacology, 2024)
Purpose: Potentially inappropriate prescribing (PIP) is commonly encountered in older adults, yet there is limited information on the occurrence of PIP among older adults with hypertension.This study aims to determine and compare the prevalence of PIP and its association with comorbidities in older adult outpatients with hypertension across hospitals and community health centers (CHCs).Methods: This 3-year (2015-2017) repeated cross-sectional study used electronic medical records from Shenzhen, China, involving 62 hospitals and 678 primary medical institutions.PIP was defined using the 2019 Beers criteria. Older adults (≥65 years) with hypertension and at least one outpatient prescription were included. Modified Poisson regression analysis was used to assess the association between chronic comorbidities, healthcare setting and PIP.The prevalence of PIP for old adult outpatients with hypertension in 2015, 2016, and 2017 was 46.32%, 46.98%, and 46.58% in hospitals, with a sample size of 38411, 46235, and 50495 respectively, and 29.14%, 26.66%, and 29.84% in CHCs, with a sample size of 26876, 29434, and 34775 respectively. The top three most popular PIP in hospitals and CHCs were proton-pump inhibitors (PPIs), diuretics, benzodiazepines and benzodiazepines, noncyclooxygenase-selective non-steroidal anti-inflammatory drugs (NSAIDs), PPIs, respectively.PIP was most associated with chronic gastrointestinal disease (adjusted prevalence ratio=1.54, 95% confidence interval=1.50-1.59) and mental and behavioral disorders (1.49, 1.46-1.53) in hospitals, and with mental and behavioral disorders (1.99, 1.95-2.03) and musculoskeletal system and connective tissue disorders (1.33, 1.31-1.36) in CHCs. The prevalence of PIP was significantly higher in hospital settings compared to CHCs (1.65,.Conclusions: Among older adult outpatients with hypertension in Shenzhen, PIP was more prevalent in hospitals than in CHCs. The comorbidities most strongly associated with PIP were chronic gastrointestinal disease and mental and behavioral disorders in hospitals, and mental and behavioral disorders in CHCs. Clinical pharmacy integration needs to be considered to reduce inappropriate prescribing in this vulnerable population.